Induced disgust increases negative implicit attitudes towards blood donation. (2nd March 2021) - Gilchrist, Philippe T.; Schnall, Simone; Vrinceanu, Tudor; Nguyen, Sebastien; Ditto, Blaine
Abstract: Background and objectives: The blood donation environment includes a variety of disgust‐related stimuli that may influence attitudes among new and prospective donors. To explore the causal role of disgust in the context of attitudes towards blood donation, we experimentally induced feelings of disgust (vs. fear, moral elevation or control). We hypothesized that for people who are generally sensitive to their bodily sensations, disgust would lead to more negative implicit attitudes towards blood donation than other emotions. Materials and methods: A total of 123 participants completed a questionnaire package including private body consciousness, disgust, altruism and social desirability. Next, participants watched one of four videos with emotional content: a video segment depicting a filthy toilet (disgust), a man chasing a woman and child wielding an axe (fear), a man whose life was positively changed by a mentor (moral elevation) or a nature documentary (control). After the video, participants completed a Single‐Target Implicit Association Test (ST‐IAT) and questions regarding explicit attitudes towards blood donation. Results: As predicted, the disgust video resulted in lower implicit attitudes towards blood donation for participants high in private body consciousness. Disgust sensitivity predicted lower donation interest, but not implicit attitudes or explicit intention. There was no effect of emotion on explicit attitudes. Conclusion: Automatic processes should be considered in the development of interventions aimed at promoting prosocial and health behaviours. Management of disgust‐related stimuli in donation centres and recruitment campaigns might improve attitudes towards blood donation.